2020
DOI: 10.1186/s12891-020-3176-x
|View full text |Cite
|
Sign up to set email alerts
|

Ilizarov external fixation for a periprosthetic tibial fracture in severe osteoporosis: a case report

Abstract: Background: The incidence of periprosthetic fractures after total knee arthroplasty (TKA) is rising due to the increasing number of TKAs performed annually and the growing elderly population. A periprosthetic fracture of the proximal tibia following TKA is a rare injury that may be a challenging clinical scenario. Case presentation: The case of an 84-year-old woman who sustained a periprosthetic tibial fracture 10 years after a TKA is presented. This patient had multiple risk factors. The fracture was not deem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This approach carries a risk of pin-tract infections. When treating periprosthetic fractures around the knee with a circular external fixator, meticulous pin care and immediate treatment with antibiotics are necessary at any sign of infection [18,[26][27][28][29][30][31][32]. Falzarano et al reported that ESR and CRP levels proved to have greater diagnostic accuracy in predicting late chronic and early postoperative infections in THA.…”
Section: Discussionmentioning
confidence: 99%
“…This approach carries a risk of pin-tract infections. When treating periprosthetic fractures around the knee with a circular external fixator, meticulous pin care and immediate treatment with antibiotics are necessary at any sign of infection [18,[26][27][28][29][30][31][32]. Falzarano et al reported that ESR and CRP levels proved to have greater diagnostic accuracy in predicting late chronic and early postoperative infections in THA.…”
Section: Discussionmentioning
confidence: 99%
“…This approach carries a risk of pin-tract infections. When treating periprosthetic fractures around the knee with a circular external fixator, meticulous pin care and immediate treatment with antibiotics are necessary at any sign of infection [18,[26][27][28][29][30][31][32]. Falzarano et al reported that ESR and CRP levels proved to have greater diagnostic accuracy in predicting late chronic and early postoperative infections in THA.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, knee joint-bridging circular hexapod external fixation carries a risk of pin-tract infections. When treating severe knee dislocation with a jointbridging circular hexapod external fixation before TKA, meticulous pin care and immediate treatment with antibiotics are necessary at the first sign of infection [19,[22][23][24][25][26][27][28]. Falzarano et al reported that ESR and CRP levels have a greater diagnostic accuracy in predicting late chronic and early postoperative infections in THA [29].…”
Section: Discussionmentioning
confidence: 99%